FACTORS AFFECTING THE LOW ACHIEVEMENT OF THE COVID-19 VACCINE AT SALAPRAYA VILLAGE, JIPUT HEALTH CENTER WORKING AREA PANDEGLANG REGENCY IN 2022 - Ma'rifatul Hayati; Titin Eka Sugihartini (Pusat Riset dan Inovasi Nasional, 2023)
Backgrounds : The vaccination program in the Jiput Puskesmas Working Area has been running according to the procedures set by the government, but in the process there are still obstacles, namely the rejection of the Covid-19 vaccine from some people, so that vaccination does not reach the expected targets. Salapraya Village has the lowest vaccination achievement among the 13 villages assisted by the Jiput Health Center, where dose 1 vaccination only reaches 35.81%, dose 2 reaches 21.31% and dose 3 reaches 0.89% of the target of 1,572 people. Purpose of Authorship: It is known that the factors that affect the low achievement of the Covid-19 vaccine at Salapraya Village, Jiput Health Center Working Area, Pandeglang Regency in 2022. Method: The research method uses a quantitative cross-sectional design. The sample of this study was the people of Salapraya Village who were targeted for Covid-19 vaccination as many as 91 people with a sampling technique using cluster sampling. Instruments use questionnaires. Data analysis using univariate and bivariate. Results: Most respondents stated that they refused to be vaccinated against Covid-19 (65.9%), had a negative perception of the Covid-19 vaccine (56%), had less knowledge about the Covid-19 vaccine (67%), and were influenced by the socio-cultural community (59.3%). There is a relationship between perception (p=0.030), knowledge (p=0.003) and socio-cultural (p=0.027) with the low achievement of the Covid-19 vaccine at Salapraya Village, Jiput Health Center Working Area, Pandeglang Regency in 2022. Conclusion and Advice: The low achievement of the Covid-19 vaccination is influenced by perception, knowledge and socio-culture. It is hoped that the public can find the right information about the Covid-19 vaccine by following the counseling provided by health workers and or utilizing existing social media and electronic media to be used as educational media to access information about the Covid-19 vaccine.